2022
DOI: 10.3390/nu14204334
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin Ameliorates High-Fat Diet-Induced Atherosclerosis in ApoE−/− Mice via Remodeling Gut Microbiota

Abstract: Capsaicin is a pungent alkaloid abundantly present in peppers with outstanding biological activities, including the anti-atherosclerosis effect. Previous studies revealed that gut microbiota played an important role in the beneficial effects of capsaicin, but whether it is essential for the anti-atherosclerosis effect of capsaicin is unclear. This study evaluated the anti-atherosclerosis effect of capsaicin in ApoE−/− mice and further explored the role of depleting gut microbiota in the improvement of atherosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…6 ). Previous studies have shown atherogenic role of Romboutsia 62,73 , and atheroprotective role of Akkermansia 62,68,73 Bifidobacterium 73,74 , Lactobacillus 74 and Turicibacter 75 in hyperlipidemic apoE -/- mouse model of atherosclerosis.…”
Section: Discussionmentioning
confidence: 91%
“…6 ). Previous studies have shown atherogenic role of Romboutsia 62,73 , and atheroprotective role of Akkermansia 62,68,73 Bifidobacterium 73,74 , Lactobacillus 74 and Turicibacter 75 in hyperlipidemic apoE -/- mouse model of atherosclerosis.…”
Section: Discussionmentioning
confidence: 91%
“…In the present study, calycosin decreased the abundance of the genus Desulfovibrio and Bilophila, thereby preventing abnormal bile acid metabolism. As Odoribacter is a conditional pathogenic bacteria, which is harmless when the balance of intestinal microbes, normal abundance in the intestine promotes butyrate production [35] . We found in our experiment, that the relative abundance of Odoribacter was significantly decreased in the HFD group, and it was speculated that HFD disrupted the balance of intestinal microbes, and Odoribacter could not synthesize butyrate in a timely manner to fight inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, fecal samples from each group (n = 6) were randomly selected for metabolomic analysis. [ 11 ] In brief, stool samples (50 mg) were solved in 400 µL methanol: water (4:1, v/v) solution containing 0.02 mg/mL L-2-chlorophenylalanin as internal standard. The mixtures were then ground by a tissue crusher (Wonbio-96c, Wanbo biotechnology, 50 Hz, 6 minutes, −10ºC) followed by ultrasonic homogenization (40 kHz, 30 minutes, 5ºC).…”
Section: Methodsmentioning
confidence: 99%